The effect of N-arachidonoylethanolamide administration on energy and fat metabolism of early lactating dairy cows - Jessica Schwerdtfeger; Helga Sauerwein; Elke Albrecht; Gemma Mazzuoli-Weber; Dirk von Soosten; Sven Dänicke; Björn Kuhla (Scientific Reports, 2023)
Abstract The aim of the study was to investigate the effect of N-arachidonoylethanolamide (AEA), an endocannabinoid with orexigenic characteristics, on plasma endocannabinoid concentrations, feed intake, energy balance, lipomobilisation, and hepatic lipid metabolism of early-lactating dairy cows. The experiment involved 10 pairs of Holstein half-sibling cows (end of 2nd–3rd pregnancy). Half-sibs of each pair were randomly assigned to either AEA (n = 10) or control (CON) group (n = 10). From day 1 to 30 postpartum, the AEA group received 5 intraperitoneal injections per week of 3 µg/kg body weight AEA and the CON group 0.9% NaCl. In week 1–3 postpartum, AEA administration had no effect on dry matter intake, body weight, or lipomobilisation, but increased plasma triglyceride concentration on d 21 p.p. and mRNA abundances of genes related to hepatic triglyceride synthesis. In week 4 postpartum, the AEA group showed reduced feed intake and whole-body carbohydrate oxidation, but increased whole-body fat oxidation and hepatic lipid accumulation, likely as a result of a counter-regulatory leptin increase. In conclusion, the present study shows a tissue-specific AEA insensitivity and may point to a leptin-controlled regulation of the ECS in early-lactation.